MESIN PENGGILING KEDELAI PEMISAH SARI PATI DARI AMPASNYA UNTUK PEMBUATAN TAHU - Arya Adjie; I Mahyudi; A Adjie; Zaldy Kurniawan; Muhammad Yunus (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The soybean milling process has problems faced by producers, namely meeting the target market, the results of the soybean milling owned by the producer are still mixed between the dregs and the starch, and must carry out the process of filtering the dregs. The purpose of this final project is to design and build a soybean grinding machine and soy starch separator from the dregs, and the resulting machine design can separate soybean starch from the dregs. The research method used is the VDI 2222 method starting with analysis, conceptualizing, designing, and completion. Based on the design results, the soybean grinding machine uses a 1 pk electric motor, the cutting eye system uses stainless material, and the filter system uses a screen. In the trail results, this machine is able to grind soybeans as much as 3kg/5min or 36kg/hour with the condition that the starch is not mixed with the dregs and the dregs are moist.